Reaction of pomegranate trees to sustained deficit irrigation in terms of morphophysiological and biochemical traits - Mohammadebrahim Nasrabadi; Asghar Ramezanian; Saeid Eshghi; Daniel Valero (Scientific Reports)
Abstract Water stress is one of the most important challenges affecting crops worldwide, particularly in arid and semi-arid regions, leading to diverse plants responses. While previous studies have examined drought responses in various crops, the mechanisms underlying vegetative responses in different pomegranate cultivars remain underexplored, particularly under varying water stress. This research investigates the effects of water scarcity on the pomegranate cultivars ‘Shishecap’ and ‘Malas-Yazdi,’ focusing on their morphophysiological and biochemical reactions to water stress conditions. Irrigation treatments included 50% of the water requirement (severe stress), 75% of the water requirement (mild stress), and 100% of the water requirement (Control). This study assessed the impact of water deficit stress on morphophysiological and biochemical characteristics, including leaf area (LA), chlorophyll (a, b, and total), carotenoid content, electrolyte leakage (EL), relative water content (RWC), proline content, soluble carbohydrates content, and the activities of catalase (CAT), superoxide dismutase (SOD), and peroxidase (POD). The results showed that EL, proline, and soluble carbohydrates content increased, whereas chlorophyll (a, b, and total), carotenoid content, RWC and LA decreased with reduced irrigation levels in both cultivars across both years. Additionally, the activities of CAT, POD, and SOD increased when the water restriction level increased. These findings suggest that the accumulation of biochemical compounds such as proline, the increased activity of antioxidant enzymes, and the reduction of LA act as adaptive mechanisms to water stress in pomegranate trees. These findings could serve as a basis for future research aimed at understanding and increasing the tolerance of pomegranate trees to water stress conditions.